Pengaruh Fasilitas Kerja dan Manajemen Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Dinas Sosial Kota Sibolga - Putri Yani; Kaharuddin Kaharuddin; Jeniusman Ahmad Hutagalung (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of work facilities and human resource management on employee performance at the Social Service Office of Sibolga City. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 42 respondents. Data analysis was carried out using validity tests, reliability tests, classical assumption tests, multiple linear regression, correlation coefficient tests, determination coefficient tests, as well as t-tests and F-tests with the help of SPSS version 26. The results show that work facilities and human resource management partially and simultaneously have a positive and significant effect on employee performance. This is proven by the t-value of work facilities (4.021) and human resource management (2.904), which are greater than the t-table value (2.02269) with a significance level of less than 0.05. Simultaneously, the F-test result is 26.413 with a significance of 0.000 < 0.05. The coefficient of determination is 0.554, indicating that 55.4% of employee performance is influenced by work facilities and human resource management, while the remaining 44.6% is influenced by other variables not examined in this study. Thus, it can be concluded that better work facilities and effective human resource management will improve employee performance at the Social Service Office of Sibolga City.